ELECTRONIC ARTS & NEW MEDIA TECHNOLOGY - UNDERWATER IMAGING - Anuar, Ayob; Aslina, Mohd Jainal; Zairun, Roslan; Sieh Ing, Hii; Nur Misha, San; Xiao Yan, Lim; Jia Qian, Chai; Sharifah Puteri Nur Athma, Wan Hazemi; Jemaah, Doli; See Kang, Tang; Daphne Lorelei, Joachim Lan; Danny Sagoh, Enteri; et al. (eART Underwater Imaging Scuba Team, FACA UNIMAS, 2024)
The Electronic Arts and New Media specialization, Fine Arts Programme, Universiti Malaysia Sarawak, through the Underwater Imaging course, takes an initiative to organize a Scuba Diving course and Coral Reef Conservation programme with Nudi Dive Centre and Fishery Department of Malaysia (Jabatan Perikanan Malaysia) for students to enhance their knowledge in underwater photography and videography, not only theoretically but also practically about the benefit of being an underwater scuba diver imaging expert who concern on ocean environment and marine life that must be protected for a future sustainability world.